Coated sodium ion battery positive electrode material as well as preparation method and application thereof

By coating the surface of the positive electrode material of sodium ion battery, the problems of low energy density and poor cycle stability of sodium ion battery are solved, and the rate performance and wide temperature cycle stability are significantly improved, especially at high temperatures performance.

CN119275262AActive Publication Date: 2025-01-07HEFEI UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411343837.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-07
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The low energy density of sodium ion batteries and poor cycle stability, especially high-temperature cycle stability, limit their development.

Method used

The surface coated sodium ion battery positive electrode material was used to coat the sodium ion battery positive electrode material, and the coated sodium ion battery positive electrode material was prepared by low-temperature heat treatment, hydrolysis and high-temperature calcination processes to improve its rate performance and wide temperature cycle stability.

Benefits of technology

It improves the chemical stability and thermal stability of the positive electrode material of sodium ion battery, reduces side reactions, improves ion transmission performance and high-temperature cycle stability, and enhances the safety and charge and discharge efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275262A_ABST
    Figure CN119275262A_ABST
Patent Text Reader

Abstract

The invention discloses a coated sodium-ion battery positive electrode material and a preparation method and application thereof, and the coated sodium-ion battery positive electrode material comprises a sodium-ion battery positive electrode material; the coating layer is formed by covering the surface of the sodium ion battery positive electrode material with a NaxAlyMgzM1-y-zO2 coating material, 0 < x < = 4, 0 < y < 1, 0 < z < 1 and y + z < = 1, and charge balance is met. According to the invention, the sodium-ion battery positive electrode material is coated, so that the safety of the sodium-ion battery positive electrode material is improved, the rate capability and the wide-temperature cycling stability, especially the high-temperature cycling stability, of the sodium-ion battery are improved, and the application of the sodium-ion battery can be further promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and specifically relates to a coated sodium ion battery positive electrode material and a preparation method thereof, and also relates to the application of the coated sodium ion battery positive electrode material in the preparation of a sodium ion battery. Background Art

[0002] Sodium-ion batteries (NIBs) are rechargeable secondary batteries that work in a similar way to lithium-ion batteries, mainly transferring charge by embedding and extracting sodium ions between the positive and negative electrodes. Sodium is an element with abundant reserves in the earth's crust. Compared with lithium resources, it is more abundant and widely distributed, which makes sodium-ion batteries have an advantage in raw material costs. With the increasing demand for large-scale energy storage systems, sodium-ion batteries have gradually gained attention. And compared with lithium-ion batteries, sodium-ion batteries have better adaptability to high and low temperatures and better safety performance.

[0003] However, the energy density of sodium-ion batteries is relatively low. In addition, their cycle stability, especially the poor high-temperature cycle stability, limits the development of sodium-ion batteries. As one of the key materials of sodium-ion batteries, the cathode material can be modified by doping, coating and other means to improve the low energy density and poor cycle stability of sodium-ion batteries.

[0004] However, it is difficult to ensure the high discharge capacity of the positive electrode material of the sodium ion battery while taking into account the stability of the cycle process in the current modification scheme. The existing modification process will either sacrifice the discharge capacity of the positive electrode material of the sodium ion battery, or ensure the discharge capacity but the improvement of the cycle stability of the positive electrode material is very limited, especially the wide temperature cycle stability. Summary of the invention

[0005] In view of this, the primary purpose of the present invention is to provide a coated sodium ion battery positive electrode material, using Na x Al y Mg z M 1-y-z O2 is used to coat the surface of the positive electrode material of the sodium ion battery to improve the safety of the positive electrode material of the sodium ion battery, and at the same time improve the rate performance and wide temperature cycle stability of the sodium ion battery, especially the high temperature cycle stability.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention first provides a coated sodium ion battery positive electrode material, comprising:

[0008] Sodium ion battery cathode materials;

[0009] and a coating layer, the coating layer being composed of Na x Aly Mg z M 1-y-z The O2 coating material is formed by covering the surface of the sodium ion battery positive electrode material, wherein 0<x≤4, 0<y<1, 0<z<1, y+z≤1 and the charge balance is satisfied.

[0010] In a further embodiment, the positive electrode material of the sodium ion battery is a layered transition metal oxide, a polyanion compound or a Prussian blue compound.

[0011] In a further embodiment, the positive electrode material of the sodium ion battery is a layered transition metal oxide.

[0012] In a further embodiment, the Na x Al y Mg z M 1-y-z In the O2 coating material, M is at least one of Zn, Cu, Nb, Ta, Si, Ge, Ti, Sn, Mo, Zr, and Ga.

[0013] The present invention further provides a method for preparing the coated sodium ion battery positive electrode material as described above, comprising the following steps:

[0014] Provide Na x Al y Mg z M 1-y-z O2 coating material precursor Na x Al y Mg z M 1-y-z Cl4;

[0015] The precursor Na x Al y Mg z M 1-y-z Cl4 and the positive electrode material of the sodium ion battery are uniformly mixed in an anhydrous environment to obtain a mixture;

[0016] The mixed material is subjected to low-temperature heat treatment, hydrolysis and high-temperature calcination in sequence to obtain a coated sodium ion battery positive electrode material.

[0017] In a further embodiment, the precursor Na x Al y Mg z M 1-y-z The mass ratio of Cl4 and sodium ion battery positive electrode material powder is a:100-a, where a is a positive number less than 5.

[0018] In a further embodiment, the precursor Na x Al y Mg z M1-y-z Cl4 was prepared by ball milling.

[0019] In a further embodiment, the ball milling process is as follows: NaCl, AlCl3, MgCl2 and MCl n The precursor Na x Al y Mg z M 1-y-z Cl4; wherein 0<x≤4, 0<y<1, 0<z<1, y+z≤1 and charge balance is satisfied; n is a positive integer and 2≤n≤6.

[0020] In a further embodiment, the temperature of the low temperature heat treatment is 170° C. to 200° C., and the insulation time is 2 to 5 hours.

[0021] In a further embodiment, the hydrolysis process is to mix the product after low-temperature heat treatment with concentrated ammonia water with a pH of 10 to 13 and stir for 10 to 24 hours, and then dry it completely.

[0022] In a further embodiment, the high temperature calcination process is carried out in an air atmosphere at a calcination temperature of 400° C. to 500° C. and a holding time of 2 to 10 hours.

[0023] The present invention further provides a sodium ion battery positive electrode, comprising the coated sodium ion battery positive electrode material as described above or the coated sodium ion battery positive electrode material prepared by the preparation method described above.

[0024] The present invention further provides a sodium ion battery comprising the sodium ion battery positive electrode described above.

[0025] Beneficial effects of the present invention:

[0026] In the present invention, Na is coated on the surface of the positive electrode material of the sodium ion battery. x Al y Mg z M 1-y-z O2 materials help stabilize the structure of sodium-ion battery cathode materials during the charge and discharge process, reduce structural damage caused by volume expansion and contraction, and give sodium-ion batteries good chemical and thermal stability, which can improve the safety of sodium-ion battery cathode materials.

[0027] Coating material Na x Al y Mg z M 1-y-zO2 also has the following significant advantages: (1) it can reduce the side reactions between the positive electrode material and the electrolyte, and improve the cycle stability and rate performance of sodium-ion batteries; (2) it helps the diffusion of sodium ions in the positive electrode material, and improves the ion transport performance of the positive electrode material; (3) it has high thermal stability, and can improve the cycle stability of sodium-ion batteries under a wide temperature range, especially at high temperatures. This has promoted the development of sodium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is Na in Example 1 of the present invention 1.5 Al 0.5 Mg 0.5 O2 coated Na 0.67 Ni 0.33 Mn 0.67 O2 positive electrode and uncoated Na in comparative example 1 0.67 Ni 0.33 Mn 0.67 Rate performance test results of O2 positive electrode.

[0029] Figure 2 is Na in Example 1 of the present invention 1.5 Al 0.5 Mg 0.5 O2 coated Na 0.67 Ni 0.33 Mn 0.67 O2 positive electrode and uncoated Na in comparative example 1 0.67 Ni 0.33 Mn 0.67 O2 positive cycle performance test results. DETAILED DESCRIPTION

[0030] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0032] The first aspect of the present invention provides a coated sodium ion battery positive electrode material, comprising:

[0033] Sodium ion battery cathode materials;

[0034] and a coating layer, the coating layer being composed of Na x Al y Mg z M 1-y-zThe O2 coating material is formed by covering the surface of the sodium ion battery positive electrode material, wherein 0<x≤4, 0<y<1, 0<z<1, y+z≤ and the charge balance is satisfied.

[0035] In the present invention, Na x Al y Mg z M 1-y-z O2 coating material covers the surface of the positive electrode material of the sodium ion battery to form a coating layer. x Al y Mg z M 1-y-z O2 has a high electrical conductivity and can form a stable SEI layer on the negative electrode surface, which can improve the overall conductivity of the positive electrode material, thereby improving the charge and discharge efficiency of the sodium ion battery, effectively promoting the migration or diffusion of sodium ions in the coating layer, improving the ion transport performance of the positive electrode material, and improving the charge and discharge efficiency. x Al y Mg z M 1-y-z O2 can reduce the side reactions between the positive electrode material and the electrolyte. It also has good thermal stability, which can improve the rate performance of sodium-ion batteries and the cycle stability under wide temperature (room temperature 25°C and high temperature 65°C), especially the cycle stability under high temperature. x Al y Mg z M 1-y-z O2 helps to stabilize the structure of the positive electrode material during the charging and discharging process, reduces structural damage caused by volume expansion and contraction, has good chemical stability and thermal stability, and can improve the safety of the positive electrode material.

[0036] In the present invention, the sodium ion battery positive electrode material may be any type of sodium ion battery positive electrode material known to those skilled in the art, without particular limitation, such as layered transition metal oxides, polyanionic compounds or Prussian blue compounds.

[0037] The layered transition metal oxide described in this article is composed of MO6 octahedrons arranged in layers, and the sodium ions are located between the layers of the octahedrons forming the multilayer structure. Its general composition formula is Na x MeO2 (0<x≤1), Me is a common transition metal element, including at least one of vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Mg), nickel (Ni), and copper (Cu). Layered transition metal oxide positive electrodes are divided into P type and O type, with O3 type and P2 type being the main types. Specific examples include Na 0.67 Ni 0.33 Mn 0.67 O2、Na 0.67 Fe0.5 Mn 0.5 O2 or NaNi 0.33 Fe 0.33 Mn 0.33 O2, but not limited to it.

[0038] The polyanion compound described herein generally refers to a positive electrode material composed of sodium, a transition metal and an anion, wherein common anions include phosphate, pyrophosphate, fluorophosphate and sulfate. Specific examples that can be mentioned include NaFeP2O7 or Na4V2(PO4)3, but are not limited thereto.

[0039] The Prussian blue compound described herein refers to a positive electrode material composed of sodium, transition metal and cyanide, which has a face-centered cubic crystal structure, and the sodium ions are in a three-dimensional channel structure and coordinated pores, thus providing a good migration channel. Specific examples that can be mentioned include NaFe2[Fe3(CN)6], but are not limited thereto.

[0040] In some specific embodiments of the present invention, the positive electrode material of the sodium ion battery is a layered transition metal oxide.

[0041] In a further embodiment, the Na x Al y Mg z M 1-y-z In the O2 coating material, M is at least one of Zn, Cu, Nb, Ta, Si, Ge, Ti, Sn, Mo, Zr, and Ga. By introducing the M element into the coating material, the high temperature performance of the coated sodium ion battery positive electrode material in this article can be further improved, and these elements will not enter the interior of the base material, but only be coated on the surface of the base material, so as not to have an adverse effect on the performance of the base material itself.

[0042] The second aspect of the present invention provides a method for preparing the coated sodium ion battery positive electrode material according to the first aspect of the present invention, comprising the following steps:

[0043] Provide Na x Al y Mg z M 1-y-z O2 coating material precursor Na x Al y Mg z M 1-y-z Cl4;

[0044] The precursor Na x Al y Mg z M 1-y-zCl4 and the positive electrode material of the sodium ion battery are uniformly mixed in an anhydrous environment to obtain a mixture;

[0045] The mixed material is subjected to low-temperature heat treatment, hydrolysis and high-temperature calcination in sequence to obtain a coated sodium ion battery positive electrode material.

[0046] In the present invention, the precursor Na x Al y Mg z M 1-y-z After Cl4 is mixed with the positive electrode material of sodium ion battery, the precursor Na x Al y Mg z M 1-y-z Due to the low melting point of Cl4, the precursor is melted on the surface of the positive electrode material of the sodium ion battery in a low temperature and oxygen-free environment to achieve uniform coating; and the Cl4 in the coated material is removed by hydrolysis. - Finally, the coated sodium ion battery positive electrode material is prepared by high-temperature calcination. This coating method is simple to operate, has low energy consumption, can form a uniform coating layer, and the coating layer composition is easy to control. In addition, the coating process is highly universal and can be applied to the mainstream sodium battery positive electrode materials on the market.

[0047] In the present invention, the precursor Na x Al y Mg z M 1-y-z Cl4 was prepared by ball milling. Specifically, the process of the ball milling method is as follows: NaCl, AlCl3, MgCl2 and MCl n The precursor Na x Al y Mg z M 1-y-z Cl4; wherein n is a positive integer and 2≤n≤6.

[0048] In the present invention, the precursor Na x Al y Mg z M 1-y-z The mass ratio of Cl4 and the sodium ion battery positive electrode material is a:100-a, wherein a is a positive number less than 5, for example, it can be any mass ratio of 1:99, 1.5:98.5, 2:98, 3:97, 3.5:96.5, 4:96, 4.5:95.5, etc.

[0049] Furthermore, the low temperature heat treatment described in this article refers to the treatment temperature just enough to make the coated precursor Na x Al yMg z M 1-y-z Cl4 melts and has no effect on the sodium ion battery cathode material in the matrix, such as causing state changes or reactions of the sodium ion battery cathode material. Generally, according to the precursor Na x Al y Mg z M 1-y-z The melting point of Cl4 is adjusted and optimized. In some specific embodiments of the present invention, the temperature of the low-temperature heat treatment is 170°C to 200°C, and the insulation time is 2 to 5 hours.

[0050] Furthermore, the Cl ions in the coated precursor can be removed by hydrolysis. Specifically, in the present invention, the hydrolysis process is to mix the product after low-temperature heat treatment with concentrated ammonia water with a pH of 10 to 13 and stir for 10 to 24 hours, and then dry it completely. The specific drying conditions can be conventional in the art, for example, it can be dried at 80°C to 150°C.

[0051] The specific reaction process is as follows:

[0052] Na x Al y Mg z M 1-y-z Cl4+NH3·H2O→Na x Al y Mg z M 1-y-z O2+HCl+NH3.

[0053] Furthermore, the high temperature calcination process is in an air atmosphere, with a calcination temperature of 400° C. to 500° C. and a holding time of 2 to 10 hours.

[0054] The third aspect of the present invention provides a sodium ion battery positive electrode, comprising the coated sodium ion battery positive electrode material as described above or the coated sodium ion battery positive electrode material prepared by the preparation method as described above. It is understandable that the sodium ion battery positive electrode also includes additives such as conductive agents and binders and materials such as positive electrode current collectors, but since these can all adopt the conventional compositions of positive electrodes in the field, there is no particular limitation.

[0055] A fourth aspect of the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode as described above. It is understood that the sodium ion battery also includes a negative electrode, a separator and an electrolyte, etc., but since these can all adopt the conventional composition of sodium ion batteries in the art, there is no particular limitation.

[0056] The present invention is described below by means of specific examples. It should be noted that the following specific examples are only for illustrative purposes and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial channels.

[0057] Example 1

[0058] This embodiment provides a Na 1.5 Al 0.5 Mg 0.5 O2 coated P2 type Na 0.67 Ni 0.33 Mn 0.67 O2 positive electrode material, the specific preparation method is as follows:

[0059] S1. Add NaCl, AlCl3, and MgCl2 into a ball mill at a molar ratio of 1.5:0.5:0.5 and mill at a speed of 500 r / min for 10 h. Mix well and crush the product to obtain a precursor Na with a particle size of 500 nm. 1.5 Al 0.5 Mg 0.5 Cl4;

[0060] S2, P2 type Na 0.67 Ni 0.33 Mn 0.67 O2 cathode powder and precursor Na 1.5 Al 0.5 Mg 0.5 Cl4 was mixed evenly in a mortar in an inert atmosphere at a mass ratio of 98:2. The mixed sample was heated to 200°C in a vacuum test tube and kept warm for 2 h. 1.5 Al 0.5 Mg 0.5 Cl4 will melt and evenly coat the surface of the positive electrode material to obtain a fast ion conductor Na 1.5 Al 0.5 Mg 0.5 Cl4 coated P2 type Na 0.67 Ni 0.33 Mn 0.67 O2 positive electrode;

[0061] S3. Put Na 1.5 Al 0.5 Mg 0.5 Cl4-coated P2-type Na 0.67 Ni 0.33 Mn 0.67 The O2 positive electrode material was added into 1 mol / L concentrated ammonia water, with a liquid-to-solid ratio of 1:20, and the temperature was set at 40℃ and stirred for 24 hours for hydrolysis.1.5 Al 0.5 Mg 0.5 Cl4 reacts to form Na 1.5 Al 0.5 Mg 0.5 O2; then put the hydrolyzed sample into a blast drying oven for 24 hours until the concentrated ammonia solution is completely dried to obtain the hydrolyzed Na 1.5 Al 0.5 Mg 0.5 O2 coated P2 type Na 0.67 Ni 0.33 Mn 0.67 O2 positive electrode;

[0062] S4, the Na 1.5 Al 0.5 Mg 0.5 O2 coated P2 type Na 0.67 Ni 0.33 Mn 0.67 The O2 positive electrode was placed in a muffle furnace and heated to 600°C and kept warm for 4 hours to obtain Na 1.5 Al 0.5 Mg 0.5 O2 surface coated with P2 type Na 0.67 Ni 0.33 Mn 0.67 O2 positive electrode material.

[0063] Comparative Example 1

[0064] This comparative example adopts the same implementation as Example 1, with the only difference being that no coating layer is formed.

[0065] Example 2

[0066] This embodiment adopts the same implementation method as that of embodiment 1, except that: in step S2, P2 type Na 0.67 Ni 0.33 Mn 0.67 O2 cathode powder and precursor Na 1.5 Al 0.5 Mg 0.5 The mass ratio of Cl4 is 99:1. Other process conditions and steps are the same as those in Example 1.

[0067] Example 3

[0068] This embodiment adopts the same implementation method as that of embodiment 1, except that: in step S2, P2 type Na 0.67 Ni 0.33 Mn 0.67 O2 cathode powder and precursor Na 1.5 Al 0.5 Mg0.5 The mass ratio of Cl4 is 96:4. Other process conditions and steps are the same as those in Example 1.

[0069] Comparative Example 2

[0070] This comparative example adopts the same implementation as Example 1, except that the coating layer formed is NaAlO2. Other process conditions and steps are the same as those in Example 1.

[0071] The specific preparation method of the coated sodium ion battery positive electrode material in this comparative example is as follows:

[0072] S1. Add NaCl and AlCl3 in a molar ratio of 1:1 into a ball mill at a speed of 500 r / min for 10 h. While mixing evenly, the product can be crushed to obtain a precursor NaAlCl4 with a particle size of 500 nm.

[0073] S2, P2 type Na 0.67 Ni 0.33 Mn 0.67 The O2 cathode powder and the precursor NaAlCl4 were mixed evenly in a mortar in an inert atmosphere at a mass ratio of 98:2. The mixed sample was heated to 200 °C in a vacuum test tube and kept warm for 2 h. At this time, NaAlCl4 would melt and evenly coat the surface of the cathode material to obtain a fast ion conductor NaAlCl4 coated P2 type Na 0.67 Ni 0.33 Mn 0.67 O2 positive electrode;

[0074] S3, NaAlCl4 coated P2 type Na 0.67 Ni 0.33 Mn 0.67 The O2 positive electrode material was added to 1 mol / L concentrated ammonia water with a liquid-to-solid ratio of 1:20 and stirred at 40°C for 24 hours for hydrolysis. During the process, ammonia water reacted with NaAlCl4 to generate NaAlO2. The hydrolyzed sample was then placed in a blast drying oven and dried for 24 hours until the concentrated ammonia solution was completely dried to obtain the hydrolyzed NaAlO2-coated P2-type Na 0.67 Ni 0.33 Mn 0.67 O2 positive electrode;

[0075] S4, the hydrolyzed and dried NaAlO2 is coated with P2 type Na 0.67 Ni 0.33 Mn 0.67 The O2 positive electrode was placed in a muffle furnace and heated to 600°C and kept warm for 4 hours to obtain NaAlO2 surface coated with P2 type Na 0.67 Ni 0.33 Mn 0.67O2 positive electrode material.

[0076] Example 4

[0077] This embodiment provides a Na 1.5 Al 0.5 Mg 0.5 O2 coated O3 type NaNi 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material, the specific preparation method is as follows:

[0078] S1, same as in Example 1;

[0079] S2, O3 type NaNi 0.33 Fe 0.33 Mn 0.33 O2 cathode powder and precursor Na 1.5 Al 0.5 Mg 0.5 Cl4 was mixed evenly in a mortar in an inert atmosphere at a mass ratio of 98:2. The mixed sample was heated to 200°C in a vacuum test tube and kept warm for 2 h. 1.5 Al 0.5 Mg 0.5 Cl4 will melt and evenly coat the surface of the positive electrode material to obtain a fast ion conductor Na 1.5 Al 0.5 Mg 0.5 Cl4-coated O3-type NaNi 0.33 Fe 0.33 Mn 0.33 O2 positive electrode;

[0080] S3, same as in Example 1;

[0081] S4, the Na 1.5 Al 0.5 Mg 0.5 O2 coated O3 type NaNi 0.33 Fe 0.33 Mn 0.33 The O2 positive electrode was placed in a muffle furnace and heated to 600°C and kept warm for 4 hours to obtain Na 1.5 Al 0.5 Mg 0.5 O2 surface coated with O3 type NaNi 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material.

[0082] Comparative Example 3

[0083] This comparative example adopts the same implementation as Example 4, with the only difference being that no coating layer is formed.

[0084] Example 5

[0085] This embodiment adopts the same implementation as that of embodiment 1, except that the positive electrode material of the sodium ion battery used is P2 type Na 0.67 Fe 0.5 Mn 0.5 O2, and its precursor Na 1.5 Al 0.5 Mg 0.5 The mass ratio of Cl4 is 98:2. The other process conditions and steps are the same as those in Example 1. The prepared coated sodium ion battery positive electrode material is Na 1.5 Al 0.5 Mg 0.5 O2-coated P2-type Na 0.67 Fe 0.5 Mn 0.5 O2 positive electrode.

[0086] Example 6

[0087] This embodiment adopts the same implementation as that of embodiment 1, except that the positive electrode material of the sodium ion battery used is Na3V2(PO4)3 positive electrode, and it is 1.5 Al 0.5 Mg 0.5 The mass ratio of Cl4 is 98:2. The other process conditions and steps are the same as those in Example 1. The prepared coated sodium ion battery positive electrode material is Na 1.5 Al 0.5 Mg 0.5 O2-coated Na3V2(PO4)3 cathode.

[0088] Comparative Example 4

[0089] This comparative example adopts the same implementation as Example 6, with the only difference being that no coating layer is formed.

[0090] Example 7

[0091] This embodiment adopts the same implementation as that of embodiment 1, except that the positive electrode material of the sodium ion battery used is NaFe2[Fe3(CN)6] positive electrode, and it is 1.5 Al 0.5 Mg 0.5 The mass ratio of Cl4 is 98:2. The other process conditions and steps are the same as those in Example 1. The prepared coated sodium ion battery positive electrode material is Na 1.5 Al 0.5 Mg 0.5 O2-coated NaFe2[Fe3(CN)6] cathode.

[0092] Comparative Example 5

[0093] This comparative example adopts the same implementation as Example 7, with the only difference being that no coating layer is formed.

[0094] Examples 8-12

[0095] Examples 8-12 all adopt the same implementation as Example 1, with the only difference being that the coating materials used are different from those in Example 1, as shown in Table 1. Each coating material is prepared in the same manner as in Example 1 according to its specific composition and ingredients.

[0096] Performance Testing

[0097] The coated sodium ion battery positive electrode materials prepared in Examples 1 to 12 and Comparative Examples 1 to 5 were prepared into sodium ion button batteries to test the electrochemical performance. The preparation method of sodium battery is as follows:

[0098] The coated sodium ion battery positive electrode material, acetylene black and PVDF are added into a ball mill in a mass ratio of 8:1:1 and ball milled for 30 minutes to form a uniform slurry. A certain amount of NMP needs to be added as a diluent before mixing. After mixing, the slurry is evenly coated on the current collector aluminum foil and assembled into a button battery with the diaphragm, electrolyte and negative electrode.

[0099] Specific assembly process: Use metallic sodium as the negative electrode, the prepared sodium positive electrode as the positive electrode, and a glass microfiber filter (grade GF / A; Whatman) as the diaphragm. Each button needs to be injected with 80μL of sodium ion electrolyte using a pipette and sealed. The entire assembly process must be carried out in a glove box filled with argon gas, and the water and oxygen content must be controlled below 0.01ppm.

[0100] 1. Room temperature long cycle test: Long cycle and rate test were performed on the NEWARE battery test system, with constant current charge and discharge cycles and rates in the voltage range of 2.5-4.5V, and the electrochemical test temperature was set to 25°C. Before the cycle, the battery was charged and discharged three times at a constant current of 0.1C to form a stable SEI film, and then cycled 200 times at 1C. The rate test was performed at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and 10C for five times, respectively, to test the discharge capacity at different current densities, and finally returned to 0.1C for five cycles to observe the battery's return performance after the high rate test.

[0101] 2. High temperature long cycle test: Long cycle test is performed on the NEWARE battery test system. Before the test, a thermostat is connected and the temperature is set to 65°C. First, a constant current charge and discharge cycle is performed 3 times at room temperature with a voltage range of 2.5-4.5V to form a stable SEI film, and then the battery is transferred to a high temperature box (65°C) and cycled 50 times at a current density of 0.5C.

[0102] The test results are shown in Table 1 and Figure 1-2 As shown in Table 1, the capacity retention rate of 200 cycles at 1C at room temperature (25°C), the discharge capacity at 10C rate at room temperature (25°C), and the capacity retention rate of 50 cycles at 0.5C at high temperature (65°C) are shown.

[0103] Table 1 Sodium ion battery performance test results

[0104]

[0105] Figure 1 and Figure 2 The test results of the rate performance and cycle performance of the coated sodium ion battery positive electrode material in Example 1 and the uncoated sodium ion battery positive electrode material in the comparative example at room temperature 25°C are shown. It can be seen that the rate performance and cycle stability at room temperature 25°C are significantly improved by coating the coating material in the present invention. Further, it can be seen from the test results in Table 1 that the coated sodium ion battery positive electrode material in the present invention not only has a higher discharge capacity, but also improves the wide temperature cycle performance, and the cycle stability at room temperature 25°C and high temperature 65°C is improved.

[0106] Based on the above results, it can be seen that the coated sodium ion battery positive electrode material provided in the present invention can improve the wide temperature cycle performance of the sodium ion battery while ensuring the rate performance, thereby further promoting the development of sodium ion batteries.

[0107] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0108] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A coated sodium ion battery positive electrode material, characterized in that: include: Sodium ion battery cathode materials; and a coating layer, the coating layer being composed of Na x Al y Mg z M 1-y-z The O2 coating material is formed by covering the surface of the sodium ion battery positive electrode material, wherein 0<x≤4, 0<y<1, 0<z<1, y+z≤1 and the charge balance is satisfied.

2. The coated sodium ion battery positive electrode material according to claim 1, characterized in that The positive electrode material of the sodium ion battery is a layered transition metal oxide, a polyanion compound or a Prussian blue compound; Preferably, the sodium ion battery positive electrode material is a layered transition metal oxide.

3. The coated sodium ion battery positive electrode material according to claim 1, characterized in that The Na x Al y Mg z M 1-y-z In the O2 coating material, M is at least one of Zn, Cu, Nb, Ta, Si, Ge, Ti, Sn, Mo, Zr, and Ga.

4. A method for preparing a coated sodium ion battery positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Provides Na x Al y Mg z M 1-y-z O2 coating material precursor Na x Al y Mg z M 1-y-z Cl4; The precursor Na x Al y Mg z M 1-y-z Cl4 and sodium ion battery cathode material powders are uniformly mixed in an anhydrous environment to obtain a mixture; The mixed material is sequentially subjected to low-temperature heat treatment, hydrolysis and high-temperature calcination to obtain a coated sodium ion battery positive electrode material; Preferably, the precursor Na x Al y Mg z M 1-y-z The mass ratio of Cl4 and the sodium ion battery positive electrode material is a:100-a, where a is a positive number less than 5.

5. The preparation method according to claim 4, characterized in that: The precursor Na x Al y Mg z M 1-y-z Cl4 was prepared by ball milling; Preferably, the ball milling process is: NaCl, AlCl3, MgCl2 and MCl n The precursor Na x Al y Mg z M 1-y-z Cl4; Among them, 0<x≤4, 0<y<1, 0<z<1, y+z≤1 and charge balance is satisfied; n is a positive integer and 2≤n≤6.

6. The preparation method according to claim 4, characterized in that: The temperature of the low-temperature heat treatment is 170° C. to 200° C., and the insulation time is 2 to 5 hours.

7. The preparation method according to claim 4, characterized in that: The hydrolysis process is to mix the product after low-temperature heat treatment with concentrated ammonia water with a pH of 10 to 13, stir for 10 to 24 hours, and then dry completely.

8. The preparation method according to claim 4, characterized in that: The high-temperature calcination process is in an air atmosphere, with a calcination temperature of 400° C. to 500° C. and a heat preservation time of 2 to 10 hours.

9. A sodium ion battery positive electrode, characterized in that: Contains the coated sodium ion battery positive electrode material as described in any one of claims 1 to 3 or the coated sodium ion battery positive electrode material prepared by the preparation method as described in any one of claims 4 to 8.

10. A sodium ion battery, characterized in that: A sodium ion battery positive electrode comprising the positive electrode of claim 9.

Citation Information

Patent Citations

  • Method for preparing sodium battery positive electrode material with high-configuration entropy surface layer by solid phase method

    CN116435481A

  • Preparation method and application of LiAlO2 coated positive electrode material

    CN118281190A

  • Coated sodium ion battery positive electrode material, preparation method and sodium ion battery

    CN118507677A

  • High-cycle sodium-ion battery positive electrode material and preparation method thereof, positive electrode plate and sodium-ion battery

    CN118970005A